Pembentukan Karakter Peserta Didik Melalui Kuliah Kerja Lapangan (KKL) Taman Nasional Baluran Banyuwangi - Khoirotun Nisail Fitriyah; Roby Firmandil Diharjo (STIKes Ibnu Sina Ajibarang, 2024)
Character must be formed through various activities. KKL is one of the activities carried out through learning outside the classroom. The purpose of this study was to determine the character building of students through field work activities (KKL) in the Baluran Banyuwangi national park area. The research method is descriptive qualitative. The research subjects were fourth semester students of Zainul Hasan Islamic University Genggong. The results showed that students have good character. The results of student data have a high percentage level of character building indicators of 85%. The percentage is based on the activities of students during the MPA activities. The highest indicators are mutual cooperation and self-confidence. Learners successfully apply character building very well.